2006
DOI: 10.1021/la060137o
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-in-a-Silica-Crust Membranes:  Macroporous Materials with Tunable Surface Functionality

Abstract: We report on alkaline hydrolysis of tetraethoxysilane (Stöber synthesis) inside a macroporous polymer matrix resulting in a homogeneous coverage of silica onto the polymer surface. The encapsulation of the polymer struts by a continuous silica crust allows further functionalization with hydrophilic and hydrophobic silylating agents. The porous silica polymeric hybrid material combines the morphological control and mechanical flexibility of the polymeric matrix with the convenient surface modifications develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Extensive review of these topics is beyond the scope of this paper. The reader, however, can find more in research [138,[146][147][148][149][150] and patent literature [151][152][153]…”
Section: Blood Purification Systems Using Affinity Membranesmentioning
confidence: 99%
“…Extensive review of these topics is beyond the scope of this paper. The reader, however, can find more in research [138,[146][147][148][149][150] and patent literature [151][152][153]…”
Section: Blood Purification Systems Using Affinity Membranesmentioning
confidence: 99%
“…Polymeric materials cannot as easily be chemically modified as silica, but it was recently shown that PES membranes can be encapsulated in silica by performing Stöber synthesis directly onto the polymer [23]. Here, we show that the addition of Bindzil silica nanoparticles results in a smooth, complete coverage of the membranes leaving a large silica surface available for functionalization with organosilanes.…”
Section: Introductionmentioning
confidence: 59%
“…In the first method, amorphous silica was synthesized directly onto the membranes. The PES-membranes were soaked in an ammonia solution (10 mL, 25% in 40 mL ethanol) for approximately 1 h before placing them in between two filter papers soaked in TEOS (10 vol% in ethanol) [23]. To allow the reagents to be homogeneously absorbed, the PES-membranes were carefully blotted, and left for 4 h in a covered Petri dish.…”
Section: Thiol-functionalization and Gold Adsorption Onto Pes-membranmentioning
confidence: 99%
“…Further current examples are silicacoated polymers that can be produced in all kinds of shapes, similar to diatom cell wall morphologies [225]. The advanced freeze casting process invented by Tomsia and colleagues has been shown to produce three-dimensional laminar structures that look quite similar to mollusk shell nacre or microporous hydroxyapatite [222].…”
Section: The Biomimetic Approachmentioning
confidence: 99%